2006
DOI: 10.1007/s00438-006-0166-0
|View full text |Cite
|
Sign up to set email alerts
|

Molecular genetic analysis of five spike-related traits in wheat using RIL and immortalized F2 populations

Abstract: Kernel number per spike is one of the most important yield components of wheat. To map QTLs related to kernel number including spike length (SPL), spikelet number per spike (SPN), fertile spikelet number (FSPN), sterile spikelet number (SSPN) and compactness, and to characterize the inheritance modes of the QTLs and two-locus interactions, 136 recombinant inbred lines (RILs) derived from 'Nanda2419' x 'Wangshuibai' and an immortalized F(2 )population (IF(2)) generated by randomly permutated intermating of thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
115
0
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(143 citation statements)
references
References 49 publications
(63 reference statements)
20
115
0
3
Order By: Relevance
“…Comparative analysis with the known major QTL for yield in wheat: A survey of the literature reporting QTL for GY and related agronomic traits in both tetraploid and hexaploid wheat (Li et al 2002;Peng et al 2003;Elouafi and Nachit 2004;Huang et al 2004Huang et al , 2006McCartney et al 2005;Quarrie et al 2005Quarrie et al , 2007Marza et al 2006;Narasimhamoorthy et al 2006;Kuchel et al 2007;Kumar et al 2007;Ma et al 2007) revealed rather different scenarios for the two major GY QTL identified in our study. Our comparative analysis was carried out by relating the (LOD À 1) supporting interval of the QTL to the Ta-SSR-2004 consensus map (Somers et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Comparative analysis with the known major QTL for yield in wheat: A survey of the literature reporting QTL for GY and related agronomic traits in both tetraploid and hexaploid wheat (Li et al 2002;Peng et al 2003;Elouafi and Nachit 2004;Huang et al 2004Huang et al , 2006McCartney et al 2005;Quarrie et al 2005Quarrie et al , 2007Marza et al 2006;Narasimhamoorthy et al 2006;Kuchel et al 2007;Kumar et al 2007;Ma et al 2007) revealed rather different scenarios for the two major GY QTL identified in our study. Our comparative analysis was carried out by relating the (LOD À 1) supporting interval of the QTL to the Ta-SSR-2004 consensus map (Somers et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…This trait has attracted great interest in recent studies due to its importance in avoiding ear diseases. Grain number per spike is one of the most important yield components of wheat (Ma et al, 2007), which was associated with the largest number of markers evaluated, i.e., five (Table 5). The specific marker for grain number was barc101 (2BL), which has not been previously associated with this trait, indicating the presence of a new QTL.…”
Section: Ssr Markersmentioning
confidence: 99%
“…The presence of QTLs near marker gwm11 for a large number of agronomic and adaptive traits has been proven by Wang et al (2009), whereas, in the present study, the only association of this marker was found with sterile spikelets per spike. Only a limited number of QTL studies for sterile spikelet number per spike have been documented (Ma et al, 2007). The coefficient of variation for sterile spikelets per spike obtained by descriptive statistics was extremely high (Table 6), probably due to the selection of a relatively small number of varieties with branched architecture of wheat spikes.…”
Section: Ssr Markersmentioning
confidence: 99%
See 1 more Smart Citation
“…Of course, these populations are associated with longer time commitments and higher costs for population construction than F 2 and backcross populations (Wan et al, 2008). Currently, the studies using an RIL as a mapping population are focused on a few crops, including rice (Wan et al, 2006), soybean (Fu et al, 2006), and wheat (Ma et al, 2007). Only limited reports were found in maize in the literature (Bouchez et al, 2002;Ordas et al, 2008), especially in China (Ding et al, 2008).…”
Section: Introductionmentioning
confidence: 99%